2019
DOI: 10.1111/jog.14111
|View full text |Cite
|
Sign up to set email alerts
|

Embryo transfer associated with hormone replacement therapy cycles using assisted reproductive technology increases placenta accreta spectrum

Abstract: Aim: To evaluate obstetric outcomes in embryo transfer (ET) during estrogen with progestin hormone replacement therapy (HRT) cycles using assisted reproductive technology (ART). Methods: Of the 118 singleton pregnancies conceived with ART and delivered between January 2015 and December 2017, we reviewed the data of 87 cases that had information on HRT at the time of ET. Data on pregnancy outcomes included the presence of small for gestational age fetuses, hypertensive disorders of pregnancy, placenta previa (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 30 publications
(31 reference statements)
1
18
1
2
Order By: Relevance
“…Another known risk factor of HDP was maternal age, including young or advanced maternal age (26), in our study, the average maternal age in OS FET group was lower than in HRT FET group, however after adjusted for maternal age and other pregnancy-related cofounders, HRT was still the risk factor of HDP while undergoing FET. Placenta accreta is a serious complication which might lead to serious perinatal obstetric outcomes even maternal death and the surgical histories of uterus and placenta previa are risk factors for placenta accrete (27). Although the rate of placenta previa was found higher in HRT FET group in our study, the frequency of placenta accrete was comparable between the two groups.…”
Section: Discussioncontrasting
confidence: 60%
“…Another known risk factor of HDP was maternal age, including young or advanced maternal age (26), in our study, the average maternal age in OS FET group was lower than in HRT FET group, however after adjusted for maternal age and other pregnancy-related cofounders, HRT was still the risk factor of HDP while undergoing FET. Placenta accreta is a serious complication which might lead to serious perinatal obstetric outcomes even maternal death and the surgical histories of uterus and placenta previa are risk factors for placenta accrete (27). Although the rate of placenta previa was found higher in HRT FET group in our study, the frequency of placenta accrete was comparable between the two groups.…”
Section: Discussioncontrasting
confidence: 60%
“…Women in the MROP-PPH group were significantly older than those in the MROP-non-PPH group and were more likely to have conceived by ART and to have undergone labor induction. The duration of the third stage of labor in the MROP-PPH group was significantly longer than that in the MROP-non-PPH group (median [interquartile range]: 26 , 19 [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], p = 0.04).…”
Section: Resultsmentioning
confidence: 99%
“…9,10,12,13,19 In the present study, the use of ART, delivery of small-for-gestationalage infant, history of abortion, and instrumental delivery were identified as independent risk factors for MROP, which is consistent with the findings of previous studies. Although ART has been recognized as a risk factor for placenta accreta and retained products of conception, [20][21][22] few studies have demonstrated that ART is an independent risk factor for retained placenta requiring MROP. 10 Currently, approximately 6% of all pregnancies in Japan, which is 5-fold more than 20 years ago, are conceived using ART, 23 indicating the possibility that cases of retained placenta requiring MROP will increase.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to endometrial pathology by TAM, embryo transfer associated with hormone replacement therapy cycles may be a cause of placenta accreta spectrum. 43 Further investigation is required to clarify the relationship between TAMrelated endometrial changes and placentation.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the perinatal outcomes of breast cancer patients, the proportion of full‐term and preterm deliveries was similar to that in women without breast cancer, but the rate of placenta accreta spectrum was 8%, being higher than that in the general population. In addition to endometrial pathology by TAM, embryo transfer associated with hormone replacement therapy cycles may be a cause of placenta accreta spectrum 43 . Further investigation is required to clarify the relationship between TAM‐related endometrial changes and placentation.…”
Section: Discussionmentioning
confidence: 99%